Survey on Wireless Sensor Networks for Reliable Life Services and Other Advanced Applications - Tarun Dubey; O.P. Sahu (IAES Indonesian Section, 2013)
Wireless is an old technology; however with the advancement of science and technology it has enabled us to send signals to one or more devices without tangible wire connections and reduced complexity. The increasing human needs have lead to the integration of different technologies into a single unit and Wireless Sensor Network (WSN) is one such integration where sensors are integrated with wireless system to form a network. This network is used for a plethora of applications in sectors like defence, agriculture, medical, environment and industry.